2018
DOI: 10.1167/iovs.18-23965
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic Stress–Induced TRPM2 Channel Activation Stimulates NLRP3 Inflammasome Activity in Primary Human Corneal Epithelial Cells

Abstract: PURPOSE. The purpose of this study was to determine whether either a hyperosmotic or oxidative stress induces NLRP3 inflammasome activation and increases in bioactive IL-1b secretion through transient receptor potential melastatin 2 (TRPM2) activation in primary human corneal epithelial cells (PHCECs). METHODS.Real-time PCR, Western blots, and immunofluorescent staining were used to evaluate TRPM2 and NLRP3, ASC, caspase-1, and IL-1b mRNA and protein expression levels, respectively. A CCK-8 assay evaluated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…More significantly, our study shows the TRPM2 channel as a key mechanism for SiNPs-induced pulmonary inflammation and lung injury. TRPM2 channel is expressed in various types of immune cells such as dendritic cells [62,63] and neutrophils [64,65], and epithelial cells [16,66,67] as well as macrophages and is important in inflammation [16,68,69]. Our in vivo evidence indicates that TRPM2 channel is critically involved in SiNPs-induced lung injury and increase in the number of mcarophages, neutrophils and lymphocytes.…”
Section: Discussionmentioning
confidence: 64%
“…More significantly, our study shows the TRPM2 channel as a key mechanism for SiNPs-induced pulmonary inflammation and lung injury. TRPM2 channel is expressed in various types of immune cells such as dendritic cells [62,63] and neutrophils [64,65], and epithelial cells [16,66,67] as well as macrophages and is important in inflammation [16,68,69]. Our in vivo evidence indicates that TRPM2 channel is critically involved in SiNPs-induced lung injury and increase in the number of mcarophages, neutrophils and lymphocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Dolunay et al showed that the inhibition of NLRP3/ASC/pro-caspase-1 inflammasome formation and activity prevents LPS-induced inflammatory hyperalgesia in mice. 54,55 However, whether IL-1β activates the NLRP3 inflammasome has seldom been studied. In this study, we showed for the first time that in NP cells, IL-1β treatment activated the NLRP3 inflammasome in time-and dose-dependent manners.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-induced TRPM2 siRNA knockdown attenuated IL-1β and IL-6 secretion. 40,41 Pro-inflammatory cytokine IL-1β is regulated by NLRP3 inflammasome and Sal treatment dramatically suppressed IL-1β expression in the liver with NAFLD. 19 NASH patients have higher IL-6 levels in serum than simple steatosis.…”
Section: Discussionmentioning
confidence: 99%